Cellular models for discovering prion disease therapeutics: Progress and challenges. Issue 2 (3rd February 2020) - Krance, Saffire H.; Luke, Russell; Shenouda, Marc; Israwi, Ahmad R.; Colpitts, Sarah J.; Darwish, Lina; Strauss, Maximilian; Watts, Joel C.
Abstract: Prions, which cause fatal neurodegenerative disorders such as Creutzfeldt‐Jakob disease, are misfolded and infectious protein aggregates. Currently, there are no treatments available to halt or even delay the progression of prion disease in the brain. The infectious nature of prions has resulted in animal paradigms that accurately recapitulate all aspects of prion disease, and these have proven to be instrumental for testing the efficacy of candidate therapeutics. Nonetheless, infection of cultured cells with prions provides a much more powerful system for identifying molecules capable of interfering with prion propagation. Certain lines of cultured cells can be chronically infected with various types of mouse prions, and these models have been used to unearth candidate anti‐prion drugs that are at least partially efficacious when administered to prion‐infected rodents. However, these studies have also revealed that not all types of prions are equal, and that drugs active against mouse prions are not necessarily effective against prions from other species. Despite some recent progress, the number of cellular models available for studying non‐mouse prions remains limited. In particular, human prions have proven to be particularly challenging to propagate in cultured cells, which has severely hindered the discovery of drugs for Creutzfeldt‐Jakob disease. In this review, we summarize the cellular models that are presently available for discovering and testing drugs capable of blocking the propagation of prions and highlight challenges that remain on the path towards developing therapies for prion disease. Abstract : The ability to propagate mouse prions in cells expressing mouse prion protein has provided a suitable paradigm for identifying compounds capable of blocking the propagation of mouse prions, as illustrated in the graphic (PrP C, cellular prion protein; PrP Sc, misfolded prion protein). In contrast, human prions have proven challenging to propagate in cultured cells, which has severely hindered the development of drugs for human prion disorders such as Creutzfeldt‐Jakob disease. In this Review article, we summarize the cellular models that are presently available for discovering and testing drugs capable of blocking the propagation of prions and highlight challenges that remain on the path towards developing therapies for prion disease.